(untitled) - Postgate, J. R. (Cambridge, 1992)
Contents: Microbes are everywhere. Normally invisible, they are abundant in the air we breathe, in soil, in water, on our skin and hair, in our mouths and intestines, and on and in the food we eat. They make the soil fertile; they clean up the environment; they change, often improve, our food; some protect us from less desirable microbes. Yet most people are scarcely aware that they exist--except when they become ill. Microbes, as "germs", are widely regarded as nasty--unpopular because a few can cause disease and a few can spoil food. Yet collectively microbes present a fascinating world of miniscule creatures, who together encompass all the processes of which terrestrial life is capable: creatures who have profound effects on our lives and surroundings. Extensively updated to include such topics as CJD, genetic manipulation, and gene therapy, this edition describes the extraordinary impact that the microbial community has on our everyday lives in an accessible and easy to read style
Keywords: Microbiology,Vi trùng học; Popular works,Các tác phẩm phổ biến